2023
DOI: 10.1088/1475-7516/2023/07/032
|View full text |Cite
|
Sign up to set email alerts
|

A consistent view of interacting dark energy from multiple CMB probes

Abstract: We analyze a cosmological model featuring an interaction between dark energy and dark matter in light of the measurements of the Cosmic Microwave Background released by three independent experiments: the most recent data by the Planck satellite and the Atacama Cosmology Telescope, and WMAP (9-year data). We show that different combinations of the datasets provide similar results, always favoring an interacting dark sector with a 95% C.L. significance in the majority of the cases. Remarkably, such a preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Many additional interesting models have been proposed to reduce the Hubble tension. These include Early Modified Gravity [109], New Early Dark Energy [103], other types of EDE [72,110,111], Stepped Dark Radiation [112,113], Interacting Dark Energy [114], Primordial Magnetic Fields [115,116] and many others. Due to finite computational resources, we could not include these models in this analysis, but we will investigate them in future works.…”
Section: Jcap04(2024)059mentioning
confidence: 99%
“…Many additional interesting models have been proposed to reduce the Hubble tension. These include Early Modified Gravity [109], New Early Dark Energy [103], other types of EDE [72,110,111], Stepped Dark Radiation [112,113], Interacting Dark Energy [114], Primordial Magnetic Fields [115,116] and many others. Due to finite computational resources, we could not include these models in this analysis, but we will investigate them in future works.…”
Section: Jcap04(2024)059mentioning
confidence: 99%
“…the Hubble tension [34,44,46,47,[69][70][71][72][73][74] while a coupled quintessence might give a different result [74,75].…”
Section: Jcap09(2023)017mentioning
confidence: 99%
“…Due to this fact, the gauged quintessence might relax the drawbacks of quintessence on Hubble tension. Also, recent studies suggest that scenarios containing the couplings between dark energy and dark matter could be a viable solution to Hubble tension [34,35,40,47,77].…”
Section: Jcap09(2023)017mentioning
confidence: 99%
See 1 more Smart Citation
“…. Recent studies [96,134] found that when using current cosmological data, the interaction could be so intense as to imply w eff,DM ∼ 1/3. We will make use of these results as a motivation to relax the constrain on Π DE , so we will allow…”
Section: Jcap11(2023)051mentioning
confidence: 99%